Comparison of the aggregation of homologous β(2)-microglobulin variants reveals protein solubility as a key determinant of amyloid formation - Pashley, Clare L. (J Mol Biol, 2016)
The mouse and human β(2)-microglobulin protein orthologs are 70 % identical in sequence and share 88 % sequence similarity. These proteins are predicted by various algorithms to have similar aggregation and amyloid propensities. However, whilst human β(2)m (hβ(2)m) forms amyloid-like fibrils in denaturing conditions (e.g. pH 2.5) in the absence of NaCl, mouse β(2)m (mβ(2)m) requires the addition of 0.3 M NaCl to cause fibrillation. Here, the factors which give rise to this difference in amyloid propensity are investigated. We utilise structural and mutational analyses, fibril growth kinetics and solubility measurements under a range of pH and salt conditions, to determine why these two proteins have different amyloid propensities. The results show that, although other factors influence the fibril growth kinetics, a striking difference in the solubility of the proteins is a key determinant of the different amyloidogenicity of hβ(2)m and mβ(2)m. The relationship between protein solubility and lag time of amyloid formation is not captured by current aggregation or amyloid prediction algorithms, indicating a need to better understand the role of solubility on the lag time of amyloid formation. The results demonstrate the key contribution of protein solubility in determining amyloid propensity and lag time of amyloid formation, highlighting how small differences in protein sequence can have dramatic effects on amyloid formation.